Correlation between mastery on the simple present tense and writing descriptive paragraph - Lidia Deviga; Yuda Fika Diliyana (English Teaching Journal : A Journal of English Literature, Language and Education, 2018)
The aim of this research was to find out the correlation between mastery on the simple present tense and writing descriptive paragraph. The method that was used in this research was a quantitative research. the subject were 42 students of the fourth semester nursing program of STIKES Bhakti Husada Mulia Madiun in the academic year 2017/2018. Simple present tense and writing descriptive paragrap test were used as the instrument for collecting the data of this research. Pearson’s Product Moment Formula was used to correlate both mastery on simple present tense (variable X) and the ability in writing descriptive text (variable Y). The result showed that there was a statistically significant correlation (0.756) is higher than the r value of significant level at 5 % (0.304). Theoretically, Null Hypothesis (Ho)is rejected and Alternative Hypothesis (Ha) is accepted. The suggestion are: the students should improve their mastery on simple present tense because it can improve their ability in expressing activities in writing.